2010
DOI: 10.15395/mkb.v42n4.28
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Tipe Staphylococcal Cassette Chromosome mec (SCCmec) Isolat Methicillin Resistant Staphylococcus aureus (MRSA)

Abstract: Abstrak

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…Studies at Universitas Padjajaran and Universitas Sriwijaya also found similar results, which showed that the predominant type was SCCmec III (89%), while SCCmec IV was 11%. 13 Research in Jambi showed similar findings where the prevalence of SCCmec III was 85.72%, SCCmec II was 7.14%, and SCCmec IV was 7.14%. 12 However, different findings were found in the majority of the pvl gene.…”
Section: Methodssupporting
confidence: 52%
See 2 more Smart Citations
“…Studies at Universitas Padjajaran and Universitas Sriwijaya also found similar results, which showed that the predominant type was SCCmec III (89%), while SCCmec IV was 11%. 13 Research in Jambi showed similar findings where the prevalence of SCCmec III was 85.72%, SCCmec II was 7.14%, and SCCmec IV was 7.14%. 12 However, different findings were found in the majority of the pvl gene.…”
Section: Methodssupporting
confidence: 52%
“…While the CA-MRSA strain has resistance only to beta-lactam antibiotics and erythromycin and, in some instances, is also resistant to quinolones. 23 A similar study at Universitas Padjajaran also showed that MRSA was resistant to gentamicin (89%), erythromycin (89%), norfloxacin (89%), and vancomycin (2%) 13 . A study conducted at H. Adam Malik Hospital Medan also showed the phenomenon of resistance to non-betalactam antibiotics such as resistance to ciprofloxacin and levofloxacin (97.5%), clindamycin, and erythromycin (45%), gentamicin (87.5%), tetracycline (62.5%), vancomycin (15%), TMP/SMX (27.5%), moxifloxacin (95%), and linezolid (2.5%).…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Resistant to gentamycin, ciprofloxacin, and clindamycin were showed in 80% of the isolates, while resistant to trimethoprim/sulfamethoxazole was showed in 74% of the isolates. Sudigdoadi (2010) showed that 89% of his isolates were resistant to gentamycin 33. question may develop the ability to destroy the antibiotic or to grow in its.…”
Section: Molecular Detectionmentioning
confidence: 99%
“…MRSA banyak tumbuh bercampur bersama MSSA (Methicillin-Sensitive Staphylococcus aureus) (Kaito et al, 2011). Menurut Ito dkk dalam(Sudigdoadi, 2010) faktor yang mendasari resistensi MRSA adalah elemen genetic yang disebut dengan Staphylococcal cassette chromosome mec (SSC-mec). 1 SSC-mec mengandung cytolisin gen psm-mec yang memicu virulensi strain HA-MRSA.…”
unclassified